University Calculus: Early Transcendentals (3rd Edition)

Published by Pearson
ISBN 10: 0321999584
ISBN 13: 978-0-32199-958-0

Chapter 13 - Section 13.1 - Functions of Several Variables - Exercises - Page 683: 62



Work Step by Step

Remember that the level curve for $f(x,y,z)=\ln (x^2+y+z^2)$ has the form of $c=\ln (x^2+y+z^2)$ ...(1) Here, we have $x=-1,y=2,z=1$ Then $c=\ln ((-1)^2+(2)+(1)^2) \implies c= \ln 4 $ Thus, equation (1), becomes: $\ln 4=\ln (x^2+y+z^2)$ This implies that $e^{\ln 4}=e^{ \ln (x^2+y+z^2)}$ Hence, $(x^2+y+z^2)=4$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.